Aplecs de fragments musicals monòdics a diversos arxius (I): Arxiu Capitular de Lleida, Arxiu Parroquial de Santa Maria del Pi, CEDOC, Museu de la Música i altres fons menors = Compilations of monodic musical fragments in various archives (I): Capitular Archive of Lleida, Parish Archive of Santa Maria del Pi, CEDOC, Barcelona Music Museum, and other smaller fonds - Massana, Joaquim Garrigosa (Miscel·lània litúrgica catalana, 2024)
The conservation of the medieval musical heritage requires the consultation, analysis and identification of its materials in order to allow research on the music and liturgies it preserves. This article deals with the materials kept at the Capitular Archive of Lleida, the Parish Archive of Santa Maria del Pi in Barcelona, the Orfeó Català Documentation Centre (CEDOC), and the Barcelona Music Museum. Information is also provided on the changes of archives of some collections of musical manuscripts.